Implementasi Pembelajaran Kooperatif Model Student Team Achievement Division untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa - Erna Lukitawati (Universitas Negeri Malang, 2022)
Abstrac: The aim of the research is to know teaching implementation type cooperative STAD to improve argue activity and achievement. This research is PTK with qualitative approach. Research subject are students of VII D SMP Negeri 1 Turen Malang which is 40 students consist of 18 female students and 22 male students. These numbers enable to make 10 group, each group consist of 4 students Result of the research of cooperative learning type STAD in mathematic learning can improve students achievement of VII D SMP Negeri 1 Turen with KKM 72, The students can achieve their study are 87,5 % with average 84, Conclution, the implementation of cooperative learning type STAD in mathematic learnng can improve students activity argue class VII D SMP Negeri 1 Turen.Keywords: opinion activities; learning achievement; stad models Abstrak: Tujuan Penelitian ini untuk mengetahui penerapan pembelajaran model kooperatif tipe STAD dalam meningkatkan aktifitas berpendapat dan prestasi belajar. Penelitian ini adalah penelitian tindakan dengan menggunakan pendekatan kualitatif. Subyek penelitian adalah siswa klas VII-D SMP Negeri 1 Turen Malang yang berjumlah 40 siswa terdiri dari 18 siswa perempuan dan 22 siswa laki-laki. jumah ini memungkinkan untuk pembagian kelompok menjadi 10 kelompok dengan jumlah anggota 4 siswa. Hasil penelitian penerapan pembelajaran kooperatif model STAD dalam pembelajaran matematika dapat meningkatkan prestasi siswa klas VII-D SMP Negeri I Turen dengan nilai KKM 72, siswa yang tuntas belajar adalah 87,5% dengan rata-rata skor 84. Simpulan, penerapan pembelajaran kooperatif Model STAD dalam pembelajaran matematika dapat meningkatkan aktifitas berpendapat siswa kelas VII-D SMP Negeri 1 TurenKata Kunci: aktifitas berpendapat; prestasi belajar; model STADThe aim of the research is to know teaching implementation type cooperative STAD to improve argue activity and achievement. This research is PTK with qualitative approach. Research subject are students of VII D SMP Negeri 1 Turen Malang which is 40 students consist of 18 female students and 22 male students. These numbers enable to make 10 group, each group consist of 4 students Result of the research of cooperative learning type STAD in mathematic learning can improve students achievement of VII D SMP Negeri 1 Turen with KKM 72, The students can achieve their study are 87,5 % with average 84, Conclution, the implementation of cooperative learning type STAD in mathematic learnng can improve students activity argue class VII D SMP Negeri 1 Turen.Keywards: opinion activities; learning achievement; stad models.